T-cell activation through immunological synapses and kinapses. - Dustin, M (2008)
T-cell activation requires 'contact' with antigen-presenting cells (APCs) to bring the T-cell receptor (TCR) and antigenic major histocompatibility complex (MHC)-peptide complex together. Contact is defined by the size of the TCR and MHC-peptide complex, which at approximately 13 nm requires extensive interdigitation of the glycocalyx of the T cell and APC. T cells may be activated through formation of a stable T cell-APC junction, referred to as an immunological synapse. It has also been shown in vitro that T cells can integrate signals from APCs without a stable interaction. In vivo imaging studies supported the importance of both motile and stable T cell-APC interactions in T-cell priming. We have found that stability depends not upon turning off motile machinery but by symmetrization of force-generating structures to balance forces and hold the cell in place. Motility is induced by breaking this symmetry, which may be necessary to maintain the differentiation potential of the T cell. Recently, we also discovered a mode of T-cell signaling leading to tolerance in vivo based purely on motile interactions. Because this entire process takes place in a state of continuous T-cell kinesis, I propose the term 'kinapse' for motile T cell-APC contacts leading to signaling. Synapses and kinapses are inter-convertible by symmetrization/symmetry breaking processes, and both modes appear to be involved in normal T-cell priming. Imbalance of synapse/kinapse states may lead to immunopathology.